Where are all the good jobs going? : what national and local job quality and dynamics mean for U.S. workers - Holzer, Harry J., 1957- (Russell Sage Foundation, 2011)
"At a time when we are desperate for any jobs at all, we must remember that the quality of work is also important. Far too many people work hard yet cannot support their families and have few prospects for upward mobility. Harry Holzer, Julia Lane, David Rosenblum, and Fredrik Andersson help us understand the trajectory of job creation in America and where good jobs come from. They utilize a unique data source that has the great virtue of including information on employers as well as the more standard measures of individual traits and hence they can study the interaction of firm and worker characteristics. They are able to describe the processes of job creation-birth and death of firms as well as their expansion and contraction-and they bring geography into the mix and show how the creation, or lack thereof, of good jobs varies by metropolitan area. This rich and detailed book will be essential for anyone interested in job quality in America."--Paul Osterman, Nanyang